Generation Z's Perspective on BCA's Persuasive Message in the "Don't Know? Kasih No!" Educational Video Campaign - Dominique Dolpin; Marsefio Luhukay (Journal of Content and Engagement, 2025)
The digital era has brought technological advances that have influenced Generation Z's lifestyle, particularly in their use of digital transaction services. As a generation familiar with technology, Generation Z is at high risk of cybercrime threats such as online fraud and personal data breaches. This study aims to explore Generation Z's perspectives on the persuasive message of the educational video "Don't Know? Kasih No!" launched by BCA. Using a qualitative approach with descriptive methods, data was collected through interviews with six informants from Generation Z. The results show that Generation Z processes the persuasive message in the educational video campaign "Don't Know? Kasih No!" through two elaboration pathways: the central route and the peripheral route, based on the message's relevance, motivation, and appeal. This study provides insights into digital communication strategies to improve data security literacy, particularly among Generation Z.